2008
DOI: 10.1017/s0265021508004699
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine causes prolonged recovery when compared with midazolam/fentanyl combination in outpatient shock wave lithotripsy

Abstract: Dexmedetomidine was associated with a longer recovery time than a midazolam/fentanyl combination when used for sedation and analgesia during outpatient extracorporeal shock wave lithotripsy in this study. The incidence of rescue sedative and analgesic need was also significantly higher when dexmedetomidine was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 21 publications
0
40
1
Order By: Relevance
“…9,11,16,17 However, Zeyneloglu et al have reported better satisfaction scores with midazolam-fentanyl combination as compared to dexmedetomidine in extracorporeal shock wave lithotripsy (ESWL) when used alone. 18 The authors also concluded that probably it was not effective as a sole agent in ESWL. In our study in spite of higher satisfaction scores in the dexmedetomidine group, both the drugs were comparable in terms of sedation as none of the patients in either group required additional sedation with propofol or any alternative anesthesia technique.…”
Section: Resultsmentioning
confidence: 99%
“…9,11,16,17 However, Zeyneloglu et al have reported better satisfaction scores with midazolam-fentanyl combination as compared to dexmedetomidine in extracorporeal shock wave lithotripsy (ESWL) when used alone. 18 The authors also concluded that probably it was not effective as a sole agent in ESWL. In our study in spite of higher satisfaction scores in the dexmedetomidine group, both the drugs were comparable in terms of sedation as none of the patients in either group required additional sedation with propofol or any alternative anesthesia technique.…”
Section: Resultsmentioning
confidence: 99%
“…[24,[31][32][33][34] The low heart rate and MAP was maintained for longer duration in group D compared to that of group M which can be explained by longer duration of action of dexmedetomidine, [24,30] as compared to that of midazolam. [18,26] These results suggest that dexmedetomidine has clinical advantage over midazolam in providing a better operative field for microscopic surgery and therefore better surgeon satisfaction. Over sedation leading to respiratory depression is an important complication during MAC.…”
Section: Discussionmentioning
confidence: 91%
“…Commonly, midazolam is given in combination with fentanyl in MAC. [16][17][18][19][20] This combination has the advantage of potentiating both hypotensive and sedative effect. It has minimal effect on heart rate as midazolam causes mild tachycardia and fentanyl causes mild bradycardia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations